2009
DOI: 10.3109/07357900903095672
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Interleukin-24 Suppresses Gastric Carcinoma Cell GrowthIn VitroandIn Vivo

Abstract: Previous studies have demonstrated that interleukin-24 [IL-24; originally called melanoma differentiation associated gene-7 (mda-7)] as a novel tumor suppressor gene has tumor-suppressive activity against a broad spectrum of human cancers. However, the therapeutic effect of the recombinant human IL-24 (rhIL-24) protein purified from prokaryotic cells on gastric cancer has not been reported. In this study, we purified soluble rhIL-24 using Q-Sepharose column after the denaturing and renaturing process from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…IL-24 is also known as melanoma differentiation-associated 7 (mda-7) due to its first discovery from human melanoma cells by combined treatment with IFN-β and MEZ (7). Studies have shown that the overproduction of IL-24 selectively inhibited cancer cell growth of diverse origins by inducing apoptosis with minimal toxicity to normal cells both in vitro and in vivo (8)(9)(10)(11)(12)(13)(14). This broad-spectrum antitumor activity of IL-24 is distinct from that of other extensively studied tumor-suppressor genes, and its growth-inhibition properties are independent of the status of p53, pRb, p21 or additional tumor-suppressor genes in cancer cells (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…IL-24 is also known as melanoma differentiation-associated 7 (mda-7) due to its first discovery from human melanoma cells by combined treatment with IFN-β and MEZ (7). Studies have shown that the overproduction of IL-24 selectively inhibited cancer cell growth of diverse origins by inducing apoptosis with minimal toxicity to normal cells both in vitro and in vivo (8)(9)(10)(11)(12)(13)(14). This broad-spectrum antitumor activity of IL-24 is distinct from that of other extensively studied tumor-suppressor genes, and its growth-inhibition properties are independent of the status of p53, pRb, p21 or additional tumor-suppressor genes in cancer cells (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterially expressed rhIL-24 protein has also been demonstrated to exert cancer-specific killing activity, providing an alternate therapeutic reagent for cancer therapy (16). rhIL-24 protein has been previously demonstrated to exert in vitro and in vivo antitumor effects in lung cancer (21) and gastric cancer (22). In the present study, the antitumor activity of bacteria-and CHO mammalian cell-derived rhIL-24 protein, and pcDNA3-hIL-24 naked plasmid were assessed in the IL-20R1/IL-20R2-expressing MDA-MB-231 human breast cancer cell line in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…rmhTNF-α and RGD-rmhTNF-α were prepared by recombinant DNA technology and were purified from Escherichia coli cell extracts as previously described [20], [21]. rmhTNF-α and RGD-rmhTNF-α were purified to 97.5% and 95% purity, respectively, by high-performance liquid chromatography.…”
Section: Methodsmentioning
confidence: 99%